Considerations for the application of series capacitors to radial power distribution circuits. - Miske, S.A (IEEE Transactions on power delivery)
This paper summarizes many of the considerations in the application of series capacitors on radial distribution circuits. The effects of series capacitors on receiving end voltages are illustrated via phasor diagrams and power-voltage characteristics. The unique voltage profile of the compensated distribution circuit is presented. Discussed are the various types of distribution circuit problems that series capacitors typically used to solve. Application guidelines are presented to help minimize oscillatory interactions with transformers and motors. The various protection schemes used in practical series capacitor banks are discussed. The information required to specify distribution series capacitor banks is outlined